Theoretical and Experimental Studies on Alkali Metal Phenoxyacetates. Issue 5 (11th July 2012) - Regulska Regulska, E. E.; Samsonowicz Samsonowicz, M. M.; Świsłocka Świsłocka, R. R.; Lewandowski Lewandowski, W. W.
Abstract : Optimized geometrical structures of alkali metal phenoxyacetates were obtained using B3LYP/6-311++G** method. Geometric and magnetic aromaticity indices, dipole moments, and energies were calculated. Atomic charges on the atoms of phenoxyacetic acid molecule and its alkali metal salts were calculated by Mulliken, APT (atomic polar tensor), NPA (natural population analysis), MK (Merz-Singh-Kollman method), and ChelpG (charges from electrostatic potentials using grid-based method) methods. The theoretical wavenumbers and intensities of IR as well as chemical shifts in NMR spectra were obtained and compared with experimental data. The effect of alkali metals on molecular structure of phenoxyacetic acid appears in the shift of selected bands along the series of alkali metal salts. The correlations between chosen bands and some metal parameters, such as electronegativity, ionization energy, and atomic, and ionic radius, have been noticed.